Comparative Study in Different Filters for Efficient Sterile Filtration. (29th July 2020) - An, Hyun Ho; Moon, Byung Seok; Park, Hyun Sik; Lee, Hong Jin; Lee, Sang Ju; Oh, Seung Jun; Kim, Bom Sahn; Lee, Byung Chul; Lee, Won Woo; Kim, Sang Eun
Abstract : Simple membrane filtration is suitable as a terminal sterilization method for radiopharmaceuticals due to their short half‐life and radiation exposure of process operator. However, it often adheres to the filter membrane and causes a considerable loss of radioactivity. We herein describe the investigation of sterile filtration performance varying individual sterile filters in order to identify the optimal sterile filter on demand for lipophilic radiopharmaceuticals. Abstract : The comparative study allowed us to establish a fully automated manufacturing process for 11 C‐PIB including the final sterile filtration process with enhanced radioactivity yield.